Choreographic training optimization of female gymnasts aged 8-11 years in aerobic gymnastics - Valentina Todorova (Kharkiv State Academy of Physical Culture, 2017)
Purpose: optimization of choreographic training of gymnasts 8-11 years old. Material & Methods: analysis of video materials; expert evaluation method; methods of mathematical statistics. Results: defined parameters choreography preparation for initial training stage. Conclusion: defined parameters that have a significant impact on the aesthetic component of movement activity athletes in aerobic gymnastics at initial training stage. Dynamics of improvement of choreographic preparedness in the experimental group confirms the advantage of the chosen technique with the use of the developed model of choreographic training of gymnasts aged 8-11 years.